Civil society regulation or silencing? examining the regulatory mechanisms for civil societies in Zimbabwe and their impact on the role of civil society organisations in the advancement of human rights - Kuveya, Lloyd (University of Pretoria, 2022)
Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2022.